FROM SILICON VALLEY TO TASHKENT: LESSONS FROM THE UNITED STATES’ TRIPLE HELIX EXPERIENCE FOR UZBEKISTAN’S INNOVATION ECOSYSTEM - Toshpulotov Shavkat Negmatullo ugli; Khusanov Salokhiddin (TADQIQOTLAR, 2026)
Abstract The Triple Helix Model conceptualises innovation as the product of dynamic interaction among universities, industry, and government. While the model has become a dominant framework in innovation studies, its practical application in transition economies remains underexplored. This article examines how the United States — widely regarded as the archetype of an advanced Triple Helix system — has institutionalised university–industry–government collaboration across federal policy, corporate practice, and higher education. Drawing lessons from the US experience, the article then analyses the current state of Uzbekistan’s innovation ecosystem, identifying the structural barriers that constrain Triple Helix development, including the legacy of Soviet-era institutional separation, weak university–industry linkages, limited research commercialisation, and human-capital outflow. The analysis is applied to a specific institutional case, the Tashkent Institute of Management and Economics (TIME), demonstrating how the framework can inform institutional strategy. The article concludes with a set of government-level policy recommendations designed to accelerate Uzbekistan’s transition toward a balanced, interactive Triple Helix configuration.